2010
DOI: 10.1021/ct1001973
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Excited State Potential Energy Surfaces on the Spatial Overlap of the Kohn−Sham Orbitals and the Amount of Nonlocal Hartree−Fock Exchange in Time-Dependent Density Functional Theory

Abstract: Time-dependent density functional theory (TDDFT) with standard GGA or hybrid exchange-correlation functionals is not capable of describing the potential energy surface of the S1 state of Pigment Yellow 101 correctly; an additional local minimum is observed at a twisted geometry with substantial charge transfer (CT) character. To investigate the influence of nonlocal exact orbital (Hartree-Fock) exchange on the shape of the potential energy surface of the S1 state in detail, it has been computed along the twist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 50 publications
3
100
0
Order By: Relevance
“…Several studies have demonstrated errors in calculated excitation energies for small lambda values and large long-range character. 50,[53][54][55][56][57] …”
Section: B Lambda Diagnosticmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated errors in calculated excitation energies for small lambda values and large long-range character. 50,[53][54][55][56][57] …”
Section: B Lambda Diagnosticmentioning
confidence: 99%
“…Several benchmark studies [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] have explored the performance of using ground-state density functionals within the adiabatic approximation for the calculation of vertically excited states using TDDFT. The scope of the previous benchmark studies has been primarily limited to singlet valence excited states [36][37][38][39] with very few benchmarks considering triplet valence [40][41][42] or singlet and triplet Rydberg excited states.…”
Section: Introductionmentioning
confidence: 99%
“…LR-TDDFT, for example, often underestimates excitation energies of charge-transfer states, 2 fails to describe excitations containing multi-electron character, and generally fails to describe the effects of dispersion. Attempts have been made to correct these features of LR-TDDFT, [4][5][6] often with some success, but it is clear that a reliable black-box method for calculating excitation energies must look beyond the HF/DFT regime.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] However, in some cases these functionals show larger errors than conventional functionals, 27 especially for calculating accurate vibrational frequencies, 28 and there is evidence to suggest that TDDFT predicts the potential energy surface less accurately compared to ground state DFT methods. 29,30 An alternative approach to such problems is to apply ground state methods directly to study excited states. While this is straightforward for the lowest energy state of a given multiplicity, for example the lowest triplet excited state (T 1 ) of a molecule with a singlet ground state, in order to compute other excited states such as the S 1 state, some modifications to the methodology are required to prevent variational collapse to the electronic ground state during the self-consistent field (SCF) process.…”
Section: Introductionmentioning
confidence: 99%